Glacial landforms in the region formerly occupied by the Haslach glacier, southern Black Forest, south-west Germany - Hofmann, Felix Martin; Berger, Alexander; Herzog, Alexander (PANGAEA, 2025)
This dataset contains ESRI shapefiles of mapped glacial landforms, i.e., initial cirques, cirques, moraines, and moraine crests in the region formerly occupied by the former Haslach glacier in the southern Black Forest (48° N, 8° E WGS 1984), south-west Germany. The last glaciation maximum ice extent of the former Haslach glacier, inferred from ice-marginal moraines, is also provided. Geomorphological mapping was undertaken for the selection of suitable sites for beryllium-10 surface exposure dating of moraine-boulder surfaces for the establishment of a regional glacier chronology. The mapping of glacial landforms in the region formerly occupied by the former Haslach glacier in the southern Black Forest involved the interpretation of derivatives of the high-resolution DGM1 digital elevation model (xy-resolution: 1 m) of the State Agency for Geoinformation and Land Development (LGL) of the state of Baden-Württemberg, freely available at: https://opengeodata.lgl-bw.de/#/(sidenav:product/3) (last access: 6 February 2025), coupled with extensive field campaigns in 2020-2022 CE. To achieve the greatest possible accuracy during the mapping of glacial landforms, exposures were inspected, if available. The shapefiles can be opened with open-source geographic information system software. The coordinate reference system of the shapefiles is EPSG 25832: ETRS89 / UTM Zone 32N (https://epsg.io/25832, last access: 6 February 2025).
Keywords: Black Forest; glacial geomorphology; Glaciation; mapping; moraine